Numerical and Comparative Study of the Turbulence Effect on Elbows and Bends for Sanitary Water Distribution (2019)
This article presents the numerical and comparative study of the effect of turbulence on elbows and bends for the parameters of an inch, by means of CFD and under the same working conditions (velocity, pressure and temperature), to determine the fluctuation in turbulence of kinetic energy between these two accessories varying the turbulence models. Two methodologies were used for this investigation, kappa-epsilon (k-ε) and kappa-omega (k-ω). The method (k- ε) is divided into three models: standard, RNG and realizable, in which turbulence of kinetic energy and of dissipation is transformed. The method (k-ω) also has three variants: standard, SST, BSL. The work presents a greater turbulence for the method of (k- ε) in kinetic energy and dissipation under the standard model for both elbow and bend, while in the method (k-ω) there is a greater turbulence of kinetic energy in the BSL model for both accessories, as in the method (k-ε) the standard model of (k-ω) represents a greater frequency turbulence.